Development of an Ocular Film Containing Ofloxacin in a Chitosan Matrix - Fauziah, Arsy; Suciati, Tri; Julianti, Elin (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2024)
Background: Chitosan is a natural polymer that is widely used in pharmaceutical applications owing to its biodegradability and biocompatibility. High molecular weight chitosan, which is commonly found in the market (Sigma Aldrich), is acid soluble and thus limits its application for ocular purposes. Objective: This study aimed to improve the characteristics of high-MW chitosan ocular films by utilizing a water-soluble, low-MW chitosan modifier for the delivery of ofloxacin post-surgery. Methods: Various film formulas were prepared using high-MW chitosan as the main polymer matrix, glycerin and polyethylene glycol 400 as plasticizers, and low-MW chitosan as film modifiers. Glycerine was the best plasticizer that produced a good film appearance when added at an appropriate ratio, 8.33 times the weight of the high MW chitosan (TGc) and 6.25 times the weight of low- and high-MW chitosan blends at (1:1) ratio (MGb). The films were further developed as TGcs and MGbs were cross-linked using sodium tripolyphosphate to control the release of ofloxacin and improve its mechanical characteristics. Water absorption capability, mechanical characteristics, in vitro drug release, and antimicrobial activity were evaluated to determine the film formula. Results: The MGb formula showed the highest water absorption (approximately 230 %), while the lowest was shown by the TGcs formula (approximately 145 %). In contrast, the TGcs formula had the highest film elasticity (141.33±8.81%), and the MGb formula had the lowest (42.55±6.11%). Surprisingly, the best controlled release of ofloxacin for up to 24 h was produced by the MGbs film, which also showed the highest antimicrobial activity. MGbs also showed moderate film characteristics, which are suitable for ocular applications. Conclusion: The research concluded that The addition of water-soluble low-MW chitosan and a cross-linker agent can improve the controlled release and characteristics of chitosan-based ocular films.